Peningkatan Kualitas Pembelajaran IPA Melalui Model Pembelajaran Problem Based Instruction (PBI) dengan Media Kartu Pintar pada Siswa Kelas III SD Negeri 64/IV Kota Jambi Semester Genap Tahun Pelajaran 2017/2018 - Yuslolita Yuslolita (Jurnal Ilmiah Universitas Batanghari Jambi, 2019)
Background problems in science learning, teachers do not involve students in investigations, students are less trained in developing work (products). The concepts mastered by students are only given by rote by the teacher, students are not taught through a process of discovery that is problem-oriented in everyday life. Based on these problems, the most appropriate solution is to implement the PBI model with smart card media. The general problem formulation is how to improve the quality of science learning in class III 64 / IV SD Negeri Jambi. Whereas specifically is whether through the Problem Based Instruction learning model with smart card media can improve teacher skills, student activities, and student learning outcomes in class III science learning at SD Negeri 64 / IV Jambi City. The general objective of this study was to improve the quality of science learning in third grade students of SD Neegri 64 / IV Jambi City. Specifically, it is to improve teacher skills, student activity, and learning outcomes in class III 64th Natural Science learning. This type of research is classroom action research, using the Problem Based Instruction model with smart card media that is applied in three cycles. Each cycle consists of two cycles with four meetings and four stages, namely planning, implementation, observation, and reflection. Subjects of the study were third grade students of SD Neegri 64 / IV Jambi City even semester 2017/2018. Data collection techniques used tests to measure learning outcomes and student activities using instruments, and observation formats for teacher management in classroom learning. The results of the study showed that for the management of learning in the classroom in cycle 1 was a score of 32, cycle 2 received a score of 38 and cycle 3 obtained a score of 48 with good criteria. The results of the study The activities of students obtain an average score of two meetings in cycle 1 is 25.85 with sufficient criteria; The cycle obtained a score of 45 with good criteria. In cycle 3, the score obtained was 34.25 in the good category. While for student learning outcomes the average percentage of classical completeness from the two meetings in cycle 1 was 56.41%. Cycle 2 obtained the percentage of classical completeness was 64%. In cycle 3, the percentage of classical completeness was 82%. The results of this study have shown that the indicators of success have been achieved so that this study was declared successful. As for the conclusions of this study, through the Problem Based Instruction (PBI) model with smart card media can improve teacher learning management, student activities and learning outcomes of class III SD Neegri 64 / IV Jambi City at even semester 2017/2018 school year.